Jakość destynacji turystycznych czynnikiem kształtującym ich konkurencyjność - Šipková, Ivana (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Quality can be one of compétitive advantages of tourism destinations. The aim of this paper isto identify the term of tourism destination quality and to emphasize its particularities. Tourism destination quality can be improved through implementation of quality management system and its competitiveness can be raised by certification of this system. It is possible to introduce three basic concepts of quality management systems in tourism destinations. Other quality management systems can be found in European tourism as well. These were established on national or international level. Although there have been identified more problems to face by implementation of quality managemen! systems, they can increase competitiveness of tourism destinations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 103-110